Cover Image Volume 48, Issue 11. (10th October 2018) - Wang, Rui; Ying, Shi
Abstract : The cover image, by Rui Wang and Shi Ying., is based on the Research Article SaaS Software Performance Issue Identification Using HMRF‐MAP Framework, https://doi.org/10.1002/spe.2607 .